Permaculture as a Reference for Curriculum Adequacy for Countryside Schools Jurisdicted by the Teaching Board of the Region of Mirante do Paranapanema/SP - Gonçalves, Moacir; Okimoto, Fernando Sérgio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The rural education is an educational methodology that pursues to link the disciplines of the Common National Curricular Base with the specificities of the knowledge and experiences of the community living in rural areas, promoting their emancipation. For this to occur, it is necessary to change the schools in rural areas, especially their Political Pedagogical Projects, which should reflect the local identity. The Brazilian education public politics created and implemented in recent years both at federal and state levels, because of a neoliberal vision, ended up directing the teaching in schools to rigid curricula, little autonomy from the teacher and disconnection between what is taught and the students experience. Consequently, the metamorphosis of rural schools into rural schools has become very difficult. In the area served by the Mirante do Paranapanema Regional Education Board there are eleven schools installed in rural settlement projects that follow traditional educational politics. Those schools could better fulfill their role as agents of social promotion if they adopted the premises of rural education. Permaculture, by working with themes from all areas of human knowledge with the objective of achieving a sustainable relationship between man and nature, can be the integrating axis for the transformation of these schools. The challenges are enormous, but the dissemination of knowledge about the references of rural education and permaculture can be the trigger to mobilize the rural and school communities to transform their schools.
Keywords: Permaculture; Rural Education; Education Political Project